A Robust and Universal Metaproteomics Workflow for Research Studies and Routine Diagnostics Within 24 h Using Phenol Extraction, FASP Digest, and the MetaProteomeAnalyzer - Heyer, Robert; Schallert, Kay; Büdel, Anja; Zoun, Roman; Dorl, Sebastian; Behne, Alexander; Kohrs, Fabian; Püttker, Sebastian; Siewert, Corina; Muth, Thilo; Saake, Gunter; Reichl, Udo; et al. (Frontiers in Microbiology, 2019)
The investigation of microbial proteins by mass spectrometry (metaproteomics) is a key technology for simultaneously assessing the taxonomic composition and the functionality of microbial communities in medical, environmental and biotechnological applications. We present an improved metaproteomics workflow using an updated sample preparation and a new version of the MetaProteomeAnalyzer software for data analysis. Multidimensional separation (GelLC, MudPIT) was sacrificed aiming at fast analysis of a broad range of different samples in less than 24 h. The improved workflow generates at least two times as many protein identifications than our previous workflow, and a drastic increase of taxonomic and functional annotations. Improvements of all aspects of the workflow, particularly the speed, make it potentially suitable for routine clinical diagnostics (i.e. fecal samples) and analysis of technical and environmental samples. The MetaProteomeAnalyzer is provided to the scientific community as a central remote server solution at www.mpa.ovgu.de.